Pengaruh Kepemimpinan, Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Kencana Hijau Binalestari - Muh. Aslam Syam Yunus; Nurman Nurman; Ilham Wardhana Haeruddin (Akuntansi, 2023)
Human resource development is needed to improv employee performance, especially at PT. Kencana Hijau Binalestari. This study aims to examine the influence of leadership, compensation, and work environment to work environment of PT. Kencana Hijau Binalestari. This research is a quantitative research is all employees of PT. Kencana Hijau Binalestari a number of 40 employees. Determination of the sample using saturated sampling technique, where the the entire population is sampled. Data analysis techniques used in this study are descriptive statistic, instrument test, classical assumption test, and hypotesis testing with mutiple linear regressionusing the help of IMB SPSS Statistic version 20 program. The result of this study partially showed that leadership has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, and work environment  has a negative and significant effect on employee performance. The result of the research simltaneously shows leaderhip, compensation, dan work environment has a positive and significant effect on employee performance at PT. Kencana Hijau Binalestari.